Exploring religious power: A re-reading of Micah’s metaphor of food (Mi 3:5) in the context of African religious space - Blessing O. Boloje (AOSIS, 2021)
Power and exploitation of power constitute an essential aspect of Micah’s oracles in the literary prophetic book, and surprisingly, exploitation of religious power was both highlighted and criticised by Micah. This article attempted to explore the religious power by reading and re-reading Micah’s metaphor of food in the context of contemporary Christian religious space in Africa that is marked by power relations, economic and material consciousness, exploitation, poverty and corruption. Clearly, images are important in people’s attempt to comprehend God and the spiritual community of which they are part, and to understand their roles. Consequently, this article employed a biblical, literary, theological and comparative method, to explore Micah’s metaphor of food in Micah 3:5 against the background of exploitative powers. In this article, the author believed that Micah’s food metaphor (Mi 3:5) is an appropriate image to capture the imagination and orientation of present-day religious leaders and Christians in Africa, and consequently, a viable medium to re-direct and inspire the work of the ministry, in a materially conscious world. The article thus demonstrated how religious power can become a vehicle for exploitation of people, for services rendered in the community.